Health Education with Slide Media and Effective Videos Increase Knowledge about Breast Care - Fikri Rizky; Wahyuningsih Wahyuningsih (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
The high incidence of breast cancer is due to the lack of awareness of women to immediately check themselves in case of abnormalities in the breast. Therefore the need for knowledge about the early prevention of breast cancer by providing health education with various media such as slides and video. The purpose of this research was to know the effectiveness of health education with slide and video media to the level of knowledge about breast care on the students of class VII and VIII. This study was a pre-experimental study with three group pre-test and post-test design. The population in this research was the students of class VII and VIII SMP 2 Kasihan which amounted to 147 people. Sampling technique in this research used total sampling. The results obtained p value 0.000 with slide media, p value 0.002 with video media, and p value 0.000 with slide and video media which means that values are smaller than the error level is 0.05 so Ha was accepted and H0 rejected. Health education with slide and video media effectively improve students' knowledge. Health education with the most effective slide media increased the knowledge of VII and VIII SMP Negeri 2 Poor students compared to video media and slide and video media.